Video Transcoder in DCT-Domain Spatial Resolution Reduction Using Low-Complexity Motion Vector Refinement Algorithm. (6th November 2008) - Tsai Tsai, Tsung-Han Tsung-Han; Lin Lin, Yu-Fun Yu-Fun; Lin Lin, Hsueh-Yi Hsueh-Yi
Abstract : We address the topic of spatial-downscaling video transcoder in DCT-domain. The proposed techniques include the hierarchical fast motion resampling (HFMR) with accuracy motion resampling, the fast refinement for nonintegral (FRNI) motion vector (MV), and the dynamic regulating search (DRS) with low-complexity motion vector refinement. Two kinds of motion vector refinement algorithms in DRS are designed for different architectures and applications. Based on brute-force motion compensation in DCT-domain (MC-DCT), FRNI can provide better quality than nonrefine MV and reduce the complexity. DRS can utilize the filter for half-pixel MV in MC-DCT and it is an efficient method for extracting MC-DCT block to improve the performance further. From the experiments, the proposed algorithms can improve the entire quality and also reduce the complexity for DCT-domain video transcoder.